The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/mph.0b013e3181468c55
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular Manifestations as Initial Presentation of Acute Leukemias in Children and Adolescents in Bahia, Brazil

Abstract: AL should be considered on the differential diagnosis of osteoarticular symptoms of unknown etiology in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…But in contrast to other reports, only 20% of the newly diagnosed ALL patients had musculoskeletal symptoms, one third of them with accompanying general complaints. Fever, pallor, bone pain and night pain are the most likely symptoms of an underlying leukaemia [9,10]. Severe night-time pains that awaken a child are not typical for JIA and point towards malignant diseases [8].…”
Section: Discussionmentioning
confidence: 99%
“…But in contrast to other reports, only 20% of the newly diagnosed ALL patients had musculoskeletal symptoms, one third of them with accompanying general complaints. Fever, pallor, bone pain and night pain are the most likely symptoms of an underlying leukaemia [9,10]. Severe night-time pains that awaken a child are not typical for JIA and point towards malignant diseases [8].…”
Section: Discussionmentioning
confidence: 99%
“…All had absence of blasts in peripheral smear which was similar to our case. Robazzi et al [11] observed arthritis in 26% occasions in a pool of 313 cases of ALL and it was mainly large joint arthritis. Marwaha et al has reported an incidence of 16% of small joints involvement in a recently published article.…”
Section: Discussionmentioning
confidence: 97%
“…Joint involvement as an initial presentation of acute leukemia in children has been described in literature [8][9][10][11]. About 15% to 30% of ALL patients manifest with osteoarthitic symptoms, some of which may mimic juvenile idiopathic arthritis (JIA) [11]. However, the interesting fact was that the arthritis here was transient and intermittent.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that childhood ALL can present with GI symptoms, such as diarrhea, but these are rarely documented and linked to ALL‐blast infiltration 10 . Even in cases of extensive leukemia infiltrates of liver/spleen/lungs, GI bleeding cannot be attributed to leukemia infiltrates but to the presence of non‐specific duodenal ulcers 11 .…”
Section: Discussionmentioning
confidence: 99%